PENGARUH STRATEGI MEDIA SOSIAL TERHADAP PENINGKATAN PENGUNJUNG DENGAN GOOGLE REVIEW SEBAGAI VARIABEL INTERVENING - Irene Nathalia Setiawan; Bambang Heriawan; Rusdiana Permanasari; Willyanto Kartiko Kusumo (ITB AAS Indonesia Surakarta, 2026)
Social media is an effective business promotion tool because it is accessible to anyone, allowing for a wider promotional network. Social media has become an indispensable tool for companies and one of the best ways to reach customers. Google reviews can also be viewed when users search for a place. When someone searches for a destination, reviews in the form of stars and words will appear. There, we can see the extent to which visitors to that destination were satisfied with the service provided. Google reviews present a significant challenge for the tourism sector. Because a destination's name is prominent and viewed by hundreds to millions of users searching for a destination, when someone searches for a destination, reviews in the form of stars and words will appear. There, we can see the extent to which visitors to that destination were satisfied with the service provided. The purpose of this study was to determine whether social media marketing has an impact on increasing visitor numbers by including Google reviews as an intervening variable.